ANALISIS PENGARUH MEREK TERHADAP KEPUTUSAN KONSUMEN DALAM PEMBELIAN SAYURAN SEGAR DI DAERAH ISTIMEWA YOGYAKARTA - , MARISA KUSUMA W ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Branding is known widely as a certain way to hold consumerâs choice over product. Marketers as well as producers of fresh vegetables nowadays seem start to do the same thing in order to bring a new perception toward consumer. Fresh vegetables which used to be merely agricultural commodities are brought into a brand new level product not only by branding itself, but also several attributes that are intially added, e.g., packaging, pricing, and information label. Although those kind of products are commonly consumed in another countries, but in Indonesia, particularly Yogyakarta region, branded fresh vegetables are still considered as premium product and only could be found in few places such as modern retails. This study was conducted to find demographics segment of branded fresh vegetables in Yogyakarta and also how branding and several attributes that attached on this product can significantly affect the consumer to choose that certain product over unbranded cheaper one. The results was processed by descriptive analysis and supported by several processing data methods. Crosstab analysis was applied for consumerâs demographics segment, the finding of attributesâ effectivity toward consumer purchasing decision applied by using conjoint analysis, and subsequently classifying factors of attribute by using factor analysis. Data was collected by inquiring 31 branded fresh vegetables consumers who were accidentally chosen in 3 modern retails in Yogyakarta. The result showed that this product was mostly chosen by female, 26-54 years old, with high household income. Moreover, information label which perceptively corellated with product quality had greater effect to get consumer attention and considerably as the most importance attribute that affected consumer purchasing decision instead of brand. Factor analysis happened to classified 9 attributes into 3 factors of attribute as follows